Notary Responsibility for Unlawfully Made Deeds in Legal Deeds of Buying and Selling Land - Rafki Ali Mahdafi; Amad Sudiro (Pusat Publikasi Nusantara, 2023)
This research discusses legal protection for buyers who have good intentions in land buying and selling transactions based on Supreme Court Decision Number 20 PK/Pid/2020. The research method used is normative juridical research with a case approach. The data used is secondary data originating from primary, secondary and tertiary legal materials. In discussions regarding sale and purchase deeds, sale and purchase agreement deeds, or power of attorney deeds to sell, it is important to apply the principle of good faith to create a sense of mutual trust between the seller and the buyer. Good faith in an objective sense means that the agreement must be implemented by complying with the norms of propriety and decency so as not to harm either party